Vibration-Fatigue Assessment On Electronics Interconnections - Wong, Zie Jen (Universiti Sains Malaysia, 2022)
Many devices consist of electronic parts and can be operated in a certain vibration environment for some instant without undergoing failure. Interconnection or joint plays a very important role in electronic devices to connect various electrical and mechanical parts altogether. Electrically conductive adhesives (ECA) are becoming a trend for the green substitute of solder as electronic interconnections. However, reliability of the ECA joint has not been adequately addressed in academic papers. The main objective of this study is to perform the vibration fatigue assessment of electrically conductive adhesive under vibration loading. Different combination of ECA materials including epoxy, silicone, and acrylate is assigned into a total of 8 simulation models with high-quality meshing. Next, modal analysis is carried out to determine the natural frequencies and mode shapes of model from 0 Hz to 2000 Hz. It is followed by the random vibration analysis and harmonic response analysis with the input PSD curve referred to JEDEC Standard. Lastly, Steinberg fatigue model is used to estimate the number of fatigue cycles and fatigue damage. Based on FEA results, maximum output of response occurs at, or near the dominate natural frequency at 1st vibration mode. This analysis helps engineers to consider changing the design to shift or even eliminate that natural frequency. On the other hand, it can be concluded that increasing elastic modulus, and thus stiffness as well as decreasing inertial mass of component can increase the fundamental frequency which in turn results in extended fatigue life. Acrylate with high elastic modulus and low mass density among polymer types can thus has highest vibration reliability to withstand vibration induced stress compared to epoxy and silicone ECAs. Overall, the effect of mechanical properties of different solder, substrates and die materials in a circuit board assembly on the vibration reliability of electrically conductive adhesive (ECA) is identified.